The Southern Sotho novel : a study of its form, theme and expression - Moloi, Alosi Johannes Mafaleng (My University, 1973)
Refer to the document
Thesis (Ph.D.(Literature)) -- University of the North, 1973
Keywords: Southern Sotho language; Sotho fiction -- History and criticism